Pengaruh Iklim Organisasi, Koordinasi dan Komitmen Organisasi Terhadap Kepemimpinan Kolektif Kolegial di Majelis Permusyawaratan Rakyat Republik Indonesia - Jazilul Fawaid (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
This research uses a quantitative research approach. The research sample was 176 respondents from a population of 313 people. Secondary data collection using literature study; Primary data collection using questionnaires and interviews. Data processing used SEM analysis and descriptive analysis which was developed with observer triangulation analysis. The results of the research analysis are 1) The magnitude of the influence of organizational climate on collective collective leadership in the People's Consultative Assembly reaches 0.67. The magnitude of the influence of coordination on the collective collective leadership in the People's Consultative Assembly reaches 0.62. The magnitude of the influence of Organizational Commitment on Collective Collective Leadership in the People's Consultative Assembly reaches 0.56; 2) Development of Concept I obtained, namely the Strategy of Organizational Support for Collective Collective Leadership in the Indonesian People's Consultative Assembly. The second concept development obtained is the optimization of the integration of roles. The development of Concept III obtained is Collegiate in the People's Consultative Assembly of the Republic of Indonesia, namely Actualization of continuing commitments.